SOCIAL REPRESENTATIONS OF TEACHERS AND STUDENTS IN THE CONTEXT OF AFFIRMATIVE ACTION POLICIES: THE EXCLUSIONARY INCLUSION (REMUNOM, 2024)
Affirmative Action Policies in higher education seek to promote social justice by using mainly social and racial quotas in access to public university. Its main challenge is to promote students' access to, material, and symbolic permanence. The objective of the study was to identify the Social Representations of quota students, non-quota holders and professors of the Nutrition course of a public university in the context of the Affirmative Action Policies. A qualitative study was carried out, whose methodological theoretical reference was the Theory of Social Representations by Moscovici. Six teachers, four student quotaters and five non-quota students, respectively, composed the focus group participated in the study. The generated statements were transcribed and submitted to Bardin content analysis. In the results, it was found that teachers, quota holders and non-quota holders understand the inclusive role of Affirmative Action Policies in higher education and the segregationist function of academic performance, regardless of the modality of student admission to university. Such segregation may be justified in the ideal of racial democracy, formal equality, academic productivism, and meritocracy, to the detriment of social and racial issues.